Human N-ras: cDNA cloning and gene structure. - Hall, A (1985)
The structure and organisation of the human N-ras gene has been determined by analysing cDNA clones derived from the two main mRNA transcripts. One clone in particular is 4.1 Kb long and originates from the larger (4.3 Kb) message. Sequence analysis of this clone has revealed that the N-ras gene consists of seven exons. A second clone deriving from the smaller (2 Kb) message shows that the difference between the two transcripts is a simple extension through the termination site of the 2 Kb transcript. Using S1 analysis, two transcriptional starts have been mapped, 10 bp apart. There is no obvious TATA box in the expected promoter region of the gene, though there are 4 GGGCGG sequences surrounding the start sites. The 5' untranslated sequence contains 2 ATGs upstream of the initiation codon.